Share market optimization : a web based system to predict share market using different kinds of economic factor - Rahat, MD. Maruf; Choudhury, Maher Mohammed Helal Uddin; Sarker, Abdur Rouf (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2008.